100 questions & answers about schizophrenia; painful minds - DeLisi, Lynn E.; Ovid Technologies, Inc. (Sudbury, Mass. : Jones and Bartlett Publishers, 2011)
Includes bibliographical references and index.
Remote
[electronic resource]
100 questions and answers about schizophrenia
One hundred questions & answers about schizophrenia
Electronic reproduction. New York, N.Y. : Ovid Technologies, Inc. Available via World Wide Web.
Keywords: Medicine; Psychiatry